(untitled) (Global Journal of Management and Business Research, 2020)
The general objective of the study was to investigate the effect of cloud computing on the performance of county governments in Kenya; a case of the county government of Nyandarua. The study#x2019;s specific objectives were to establish the influence of staff skills on performance of the County Government. The study was informed by Resource Based View Theory. The study adopted a correlational research design. The target population was 130 employees in ICT, communication, finance and administration department in the county government of Nyandarua. Simple random sampling was used to select a sample size of 97 respondents.